2019
DOI: 10.1080/17429145.2019.1645896
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis ameliorates water stress tolerance in maize and common bean

Abstract: Water stress is one important abiotic stress with negative impacts on plant productivity. In order to ameliorate abiotic stress, plant growth-promoting rhizobacteria (PGPR), such as Bacillus subtilis, can be used due to their positive effects on plant physiology. The present study aimed to evaluate the effects of B. subtilis on the performance of maize and common bean under water deficit conditions. The study was performed in a plant growth chamber and the growth, gas exchange parameters and antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…In contrast, the cell physiological analyses showed that only CAT was found to respond significantly to the FMCH001 inoculation whereas neither source nor sink metabolism was neither positively nor negatively affected as assessed via the determination of various cell and ecophysiological parameters. However, other work has shown that even effective physiological changes may be subtle and therefore difficult to capture (de Lima et al, 2019). Thus, our findings do not rule out regulation via subtle changes in specific temporal and spatial dynamics.…”
Section: Discussioncontrasting
confidence: 81%
“…In contrast, the cell physiological analyses showed that only CAT was found to respond significantly to the FMCH001 inoculation whereas neither source nor sink metabolism was neither positively nor negatively affected as assessed via the determination of various cell and ecophysiological parameters. However, other work has shown that even effective physiological changes may be subtle and therefore difficult to capture (de Lima et al, 2019). Thus, our findings do not rule out regulation via subtle changes in specific temporal and spatial dynamics.…”
Section: Discussioncontrasting
confidence: 81%
“…Traoré et al (2016) reported improved corn seed germination, plant growth, plant production (increase yield by 42%) grain and shoot P biomass content of 34 and 64%, respectively with B. subtilis inoculation (strain DSM10). Lima et al (2019) verified that B. subtilis (strains AP-3 and PRBS-1) promoted common bean (Phaseolus vulgaris L.) and corn growth, increasing the water use efficiency, leaf water content and the regulation of stomata, without damaging photosynthetic rates. Zarei et al (2019) concluded that Pseudomonas fluorescens (P1, P3, P8, and P14 -prepared from the collection of Vali-e-Asr University of Rafsanjan) can improve plant water deficit stress tolerance, P solubilization and siderophore production, leading to an increased sweet corn (Zea mays L. var saccharata) growth and yield.…”
Section: Introductionmentioning
confidence: 83%
“…Other studies also found that inoculation of plant roots with Bacillus spp. could mitigate water stress in plant species such as common bean, maize, and pepper via a decrease in stomatal conductance (Li et al, 2016 ; Samaniego-Gámez et al, 2016 ; de Lima et al, 2019 ). The effect of Bacillus on reducing stomatal conductance and transpiration during or after the moderate water stress, therefore, possibly contributed to more efficient water use or a “water-saving” outcome by the organic amendments in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a series of unpublished reports in our laboratory have consistently shown how the banding of poultry litter in poorly structured sub-surface layers of Sodosol has increased the TE of the wheat plant, although the basis for this effect on TE is not understood. Ample evidence showed that the direct inoculation of plant seeds or roots with beneficial bacteria such as Bacillus subtilis or Bacillus licheniformis FMCH001 could enhance plant photosynthetic capacity (Li et al, 2016 ; Barnawal et al, 2017 ) or reduce water stress via partial stomatal closure (de Lima et al, 2019 ; Akhtar et al, 2020 ). Possibly, organic amendments enable plants to use water more efficiently via their direct effect on soil physical and/or biological properties.…”
Section: Introductionmentioning
confidence: 99%